Hubungan Kunjungan Lapangan ke Situs Bersejarah terhadap Sikap Nasionalisme Mahasiswa Pendidikan Sejarah Universitas Mulawarman (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the relationship between visits to historical sites and nationalism attitudes of History Education students at Mulawarman University. The research background emphasizes the importance of learning history that is not only theoretical, but also based on direct experience. The method used is a quantitative approach with a correlational design, using a questionnaire as an instrument analyzed through the Spearman correlation test. The results showed that the majority of students had a level of field trips that ranged from moderate to high, with a significant positive relationship to their nationalism attitude. The obtained correlation coefficient value of 0.620 with a significance value of 0.000 (p < 0.05) indicates that the higher the frequency of field trips, the higher the students' nationalism attitude. As much as 47.4% of the results of variation in nationalism attitude can be explained by the frequency of field trips, while the rest is influenced by other factors. Thus, visits to historical sites play an important role in shaping students' nationalism attitudes.